Voices of independence: Saudi autistic adults’ lived experiences of independent living and marriage - Khalil, A.I. (Klinicheskai͡a︡ i spet͡s︡ialʹnai͡a︡ psikhologii͡a, 2025)
Abstract only Objective. This research aimed to investigate the experiences of adults with autism spectrum disorder (ASD) as they pursue independence and explore their views on romantic relationships and marriage. Methods and materials. Seven individuals with ASD and co-occurring conditions, such as anxiety, depression, and obsessive-compulsive disorder (OCD), participated in qualitative interviews. The study delved into their educational backgrounds, employment situations, and familial histories of ASD or mental health issues to identify the challenges they face and the support they need. Results. The results revealed significant obstacles, including underemployment and insufficient formal qualifications, exacerbated by co-occurring mental health issues. Despite these difficulties, participants expressed a strong desire for independence and meaningful relationships. The findings emphasize the systemic barriers that hinder autistic adults' capacity for autonomy and relationship building in educational and occupational settings. Conclusions. In conclusion, the research highlights that while autistic individuals possess unique strengths, they face considerable challenges that limit their independence and ability to form and maintain relationships. To empower autistic individuals to lead independent lives and pursue fulfilling relationships, it is essential to develop comprehensive support systems, including customized educational programs, mental health resources, and inclusive policies. Heightened public awareness, expanded specialized services, and policy initiatives that uphold the autonomy of autistic individuals are crucial. Additionally, enhanced training for healthcare professionals and relationship support programs for autistic adults are vital for improving their overall quality of life Цель. Данное исследование было посвящено изучению опыта взрослых с расстройствами аутистического спектра (РАС), ориентированных на достижение самостоятельности, а также их взглядов на романтические взаимоотношения и брак. Методы и материалы. В рамках исследования были проведены качественные интервью с семью респондентами, имеющими РАС и сопутствующие состояния, такие как тревожные расстройства, депрессия и обсессивно-компульсивное расстройство (ОКР). Для выявления проблем, с которыми сталкиваются данные лица, и анализа необходимой им поддержки были изучены их уровень образования, ситуация с трудоустройством, а также семейная история, связанная с РАС или психическими расстройствами. Результаты. Результаты исследования продемонстрировали наличие значительных препятствий, включая неполную занятость и недостаточный уровень официальной квалификации, которые усугубляются сопутствующими психическими расстройствами. Несмотря на эти трудности, участники выразили сильное стремление к достижению самостоятельности и построению значимых взаимоотношений. Полученные данные подчеркивают системные барьеры, препятствующие способности взрослых с РАС к автономии и установлению социальных связей в образовательной и профессиональной сферах. Выводы. Исследование указывает на то, что, несмотря на уникальные сильные стороны, присущие аутичным индивидуумам, они сталкиваются с серьезными проблемами, ограничивающими их независимость и способность к формированию и поддержанию отношений. Комплексная система поддержки должна включать индивидуальные образовательные программы, психиатрическую помощь и инклюзивную политику. Крайне важны повышение осведомленности, расширение специализированных служб и инициатив, поддерживающих автономию аутичных людей. Кроме того, повышение квалификации медицинских работников и разработка программ поддержки взаимоотношений для взрослых, страдающих аутизмом, имеют жизненно важное значение для улучшения их общего качества жизни.